2016
DOI: 10.1016/j.ygcen.2016.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, localization and temporal expression of crustacean hyperglycemic hormone (CHH) in the behaviorally rhythmic peracarid crustaceans, Eurydice pulchra (Leach) and Talitrus saltator (Montagu)

Abstract: Crustacean hyperglycemic hormone (CHH) has been extensively studied in decapod crustaceans where it is known to exert pleiotropic effects, including regulation of blood glucose levels. Hyperglycemia in decapods seems to be temporally gated to coincide with periods of activity, under circadian clock control. Here, we used gene cloning, in situ hybridization and immunohistochemistry to describe the characterization and localization of CHH in two peracarid crustaceans, Eurydice pulchra and Talitrus saltator. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Gene expression was performed using Taqman MGB hydrolysis probes as described previously (Hoelters et al, 2016 ) using standard curves made from in vitro transcribed cRNA. In brief, standards were made from PCR products generated using gene-specific primers 5′ flanked by T7 phage promoter sequences.…”
Section: Methodsmentioning
confidence: 99%
“…Gene expression was performed using Taqman MGB hydrolysis probes as described previously (Hoelters et al, 2016 ) using standard curves made from in vitro transcribed cRNA. In brief, standards were made from PCR products generated using gene-specific primers 5′ flanked by T7 phage promoter sequences.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, in situ hybridization in two species of crustaceans, Eurydice pulchra (Leach) and Talitrus saltator (Montagu), showed that CHH mRNA was localized in protocerebral cells [32]. …”
Section: Resultsmentioning
confidence: 99%
“…Neuropeptide localization in species and/or tissue(s) enables mapping in neuronal subtypes relative to structural components of the cell, tissue or whole organisms, which can then be used to inform the function of a target neuropeptide and to direct functional biology experiments (Hoelters et al, 2016). Overall, the rapid increase in 'omics'-derived neuropeptide sequence data has revolutionized our approach to the localization of neuropeptides and their signaling pathway components (Elphick and Mirabeau, 2014) and facilitated our ability to construct species-and neuropeptide-specific 'connectomes' (Shahidi et al, 2015).…”
Section: Methods For Neuropeptide Localizationmentioning
confidence: 99%